A Literature Review: A Comprehensive Analysis of Type 2 Diabetes Mellitus in Productive-Age Adults and Adolescents in Indonesia - Elizabeth Haryanti (Indo Publishing, 2026)
Type 2 Diabetes Mellitus (T2DM), traditionally associated with older adults, has emerged as a critical public health crisis among younger populations globally, with Indonesia representing a significant and rapidly growing epicenter. This phenomenon, where diagnosed cases represent merely the